Peritoneal Shunt Extraction in Children Using Laparoscopy: A Case Report - Arif Kusumo Rahardjo; Yusuf Hermawan; Vita Dwi Wijayanti (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2022)
Laparoscopy is one way to perform various simple procedures or surgeries in the abdominal cavity. Laparoscopy can be useful in the management of ventriculo-peritoneal shunt (VP Shunt) fractures. The peritoneal component of the shunt remaining in the abdominal cavity can be removed using laparoscopy. A pediatric patient with hydrocephalus with a history of VP Shunt insertion 5 years ago, came with complaints of weakness, vomiting and difficulty eating. Physical examination revealed the presence of edema in the chamber area. A CT scan of the head and plain abdominal radiographs were performed. The diagnosis was made as a shunt fracture, with the peritoneal component of the shunt remaining in the abdominal cavity. The patient received treatment in the form of a revised VP shunt and peritoneal shunt extraction using standard laparoscopy which is commonly used for adult patients. The patient's condition improved after the procedure. Peritoneal shunt extraction in cases of VP shunt fracture can be safely performed using laparoscopy. If there are limited tools, this procedure can still be performed on children using standard laparoscopy which is usually used for adult patients.  Authors report this case due to no previous report in Mojokerto area were known.